STRES IBU TUNGGAL YANG MEMILIKI ANAK AUTIS - Astri Nur Kusumastuti (Jurnal Psikologi, 2014)
The purpose of research to assess the stress overview single mothers who have children with autism and to determine the factors that cause stress on single mothers who have children with autism. This research was conducted using qualitative methods in the form of case studies. Source of data which is the subject of research are single mothers who have children with autism, subject is one person. Data collection techniques using non-participant observation and in-depth interviews. The results showed that the picture of a single mother who has a child with autism can cause stress in a single parent because the burden of responsibility in caring for children who are usually held by married couples to be borne alone by a single parent is the mother. The factors that cause stress single mothers can also be caused by the condition of children who have special needs, the needs of the economy and their shame with the condition themselves. Key words: Stress, Single mothers, Children with autism